2019
DOI: 10.1177/0964528419827228
|View full text |Cite
|
Sign up to set email alerts
|

Supporting informed choice in acupuncture: effects of a new person-, evidence- and theory-based website for patients with back pain

Abstract: Objectives: To test whether a newly developed person-, theory- and evidence-based website about acupuncture helps patients make informed decisions about whether or not to use acupuncture for back pain. Methods: A randomised online study compared a newly developed ‘enhanced website’ to a ‘standard website’. The enhanced website provided evidence-based information in a person-based manner and targeted psychological constructs. The standard website was based on a widely used patient information leaflet. In total,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Five studies [24,31,38,41,42] evaluated patients with either hip or knee OA. Four studies [23,30,39,43] evaluated patients with chronic back pain. One study [35] evaluated patients with knee pain, back pain, knee OA, and/or hip OA.…”
Section: Characteristics Of Study Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies [24,31,38,41,42] evaluated patients with either hip or knee OA. Four studies [23,30,39,43] evaluated patients with chronic back pain. One study [35] evaluated patients with knee pain, back pain, knee OA, and/or hip OA.…”
Section: Characteristics Of Study Participantsmentioning
confidence: 99%
“…In 13 studies [24,25,28,29,31,[34][35][36][37][38][39]41,42], patients were deciding between surgical and conservative management of chronic pain conditions, including joint replacement and back surgery. In the other four studies [23,27,30,43], patients used decision aids to decide among nonsurgical treatment options, including acupuncture, medications, injections, exercise-based therapy, and cognitive behavioral therapy.…”
Section: Types Of Decisionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review identified 17 randomized controlled trials of decision aids for chronic musculoskeletal pain, all targeting specific pain etiologies (such as hip or knee osteoarthritis). Only four decision aids addressed conservative management strategies [ 41 44 ]. Most [ 12 ] focused on decisions to undergo surgery.…”
Section: Introductionmentioning
confidence: 99%